Walls come tumbling down but not in Palestine - Abd Razak, Dzulkifli (2004)
FIFTEEN years ago in 1989, one of the world's most infamous wall was torn down. Brought about by a tidal wave of democracy sweeping throughout Germany, the borders between West and East Germany were forced opened, literally through the cracks in the Berlin Wall. Erected on the night in August 1961, the barricade of barbed wires and cinder blocks was later replaced by a series of concrete walls of up to five metres high, guarded buy watchtowers, gun emplacements and mines. In the 1980s, the system of walls, electrified fences, and fortifications divided not only the city of Berlin but extended a further 120km around West Berlin. Access between the two countries was totally closed.